Checkmate to murder : a second World War mystery - Lorac, E. C. R., 1894-1958 (British Library crime classics., 2021)
"On a dismally foggy night in Hampstead, London, a curious party has gathered in an artist's studio to weather the wartime blackout. A civil servant and a government scientist are matching wits in a game of chess, while an artist paints the portrait of his characterful sitter, bedecked in Cardinal's robes at the other end of the room. In the kitchen, the artist's sister is hosting the charlady of the miser next door. When the brutal murder of said miser is discovered by his Canadian infantryman nephew, it's not long before Inspector Macdonald of Scotland Yard is at the scene, faced with perplexing alibis and with the fate of the young soldier in his hands. In the search for the culprit, Macdonald and his team of detectives must figure out if one of the members of the studio party is somehow involved in the death, or if some other scurrilous neighbor could be responsible"--